2003
DOI: 10.1002/adma.200305490
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoribbon Microcavity Lasers

Abstract: ZnO nanoribbons with pseudo‐rectangular cross‐sections (see Figure) are demonstarted to be excellent microcavities with a high quality factor (∼ 3000). The lasing threshold is shown to be inversely proportional to the length of the ribbon for pumping intensities lower than the saturation region. Analysis of the emission spectra points to the possibility of the existence of both pure axial modes and “bow‐tie” cavity modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
178
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(182 citation statements)
references
References 20 publications
4
178
0
Order By: Relevance
“…1) which was inserted into the glass tube after applying a small amount of vacuum grease. The bottom end of this glass tube was connected to a vacuum flask through a thin rubber pipe and stop cock (2). The inset of Fig.…”
Section: Synthesis Of Ordered Zno Nanowire Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…1) which was inserted into the glass tube after applying a small amount of vacuum grease. The bottom end of this glass tube was connected to a vacuum flask through a thin rubber pipe and stop cock (2). The inset of Fig.…”
Section: Synthesis Of Ordered Zno Nanowire Arraysmentioning
confidence: 99%
“…The vacuum flask in the set-up not only prevents the solution from entering the vacuum pump but also prevents air from entering the glass tube. Further, the solution level inside the glass tube can also be easily controlled with the help of a stop cock (2). After attaining the desired vacuum (3-4 × 10 −2 torr) in the system, stopcock (1) in Fig.…”
Section: Synthesis Of Ordered Zno Nanowire Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…This geometrical arrangement enables the optical characterization of single vertical nanocavities by using a focused beamspot smaller than the distance between adjacent nanowires, as well as high-resolution photoluminescence imaging by UVlaser scanning confocal microscopy Lasing has been observed in ZnO structures including micropillars, nanowires, and nanorods. 3,[7][8][9][10][11] Investigation of the lasing characteristics of high density ZnO nanowire arrays has shown that high quality single-crystalline ZnO nanowires constitute ideal lasing nanocavities, which provide both a gain medium and a resonant cavity due to reflection at the planar endfacets. 12,13 Lasing emission of a single nanowire placed horizontally on a substrate was first demonstrated in 2001 and subsequent work has developed a further understanding of the lasing mechanism in ZnO nanostructures.…”
mentioning
confidence: 99%
“…The similar phenomenon was also observed in ZnO nanoribbon microcavity. 15 In addition, we can estimate the mode quality ͑Q͒ factor with different nanowires at 4.2 K, which is defined as the ratio of the mode wavelength to the width. 16 In Fig.…”
mentioning
confidence: 99%